Proust, class, and nation - Hughes, Edward J. (Edward Joseph), 1953- (Oxford : Oxford University Press, 2011)
Edward J. Hughes here seeks to assess how Proust and his novel 'A la Recherche du Temps Perdu' might be understood in relation to issues of class and nation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Proust, Marcel, -- 1871-1922.; Social classes in literature; Nationalism in literature